Two-Person Technique of Peroral Endoscopic Myotomy for Achalasia with an Advanced Endoscopist and a Thoracic Surgeon: Initial Experience - Madhusudhan R. Sanaka; Ramprasad Jegadeesan; Prashanthi N. Thota; Udayakumar Navaneethan; Rocio Lopez; Sudish C. Murthy; Siva Raja (Canadian Journal of Gastroenterology and Hepatology)
Background and Aims. We initiated peroral endoscopic myotomy (POEM) utilizing a two-person technique with combination of an advanced endoscopist and a thoracic surgeon with complementary skills. Our aim was to determine the feasibility and outcomes in initial 20 patients. Methods. In this observational study, main outcomes measured were therapeutic success in relieving symptoms (Eckardt score < 3), decrease in lower esophageal sphincter (LES) pressures, improvement in emptying on timed barium esophagogram (TBE), and complications. Results. POEM was successful in all 20 patients with a mean operative time of 140.1+32.9 minutes. Eckardt symptom scores decreased significantly at two-month follow-up (6.4+2.9 versus 0.25+0.45, p<0.001). Both basal and residual LES pressures decreased significantly (28.2+14.1 mmHg versus 12.8+6.3 and 22.4+11.3 versus 6.3+3.4 mmHg, p=0.025 and <0.001, resp.). Barium column height at 5 minutes on TBE reduced from 6.8+4.9 cm to 2.3+2.9 cm (p=0.05). Two patients (10%) had mucosal perforations and one had delayed bleeding (5%). Conclusions. Two-person technique of POEM with combination of an advanced endoscopist and a thoracic surgeon is highly successful with low risk of complications.